Digital Transformation in Sharia Mutual Fund Marketing: A Systematic Literature Review in Indonesia (2015–2025) - Setiawati, Liya; Istiqomah, Yuliani; Imbrani, Hari (Perkumpulan Dosen Muda (PDM) Bengkulu, 2025)
Purpose: This study aims to explore the transformation of digital strategies in the marketing of Islamic mutual funds within the context of the digital economy. This research is important due to the increasing awareness among Muslim investors to prioritize Sharia-compliant investments supported by technological advancements. Methodology: A qualitative approach using a Systematic Literature Review (SLR) was employed, supported by Watase Uake, a bibliometric software that enables article classification, keyword mapping, and thematic visualization of academic literature. Results: The review highlights that digital platforms, mobile applications, social media, and AI-powered tools are central to promoting Sharia mutual funds. Key strategies include educational campaigns, influencer-driven content, and personalized recommendations.. Findings: There is a growing engagement from Gen Z and millennial Muslim investors, alongside the adoption of technologies such as blockchain and robo-advisors to enhance transparency and trust. However, challenges remain in digital literacy, regulatory clarity, and equitable access.. Novelty: The novelty of this research lies in its comprehensive bibliometric mapping of digital marketing strategies specific to Sharia-compliant investment products. Originality: Its originality stems from synthesizing Islamic financial marketing with recent digital transformation trends. . Conclusion: The study concludes that while digital marketing opens broad opportunities, challenges in literacy, regulation, and equitable access remain. Type of Paper: Systematic Literature Review (SLR)